FFT simulations and multi-coated inclusion model for macroscopic conductivity of 2D suspensions of compound inclusions - Luat, Nguyen Van; Kien, Nguyen Trung (Vietnam Journal of Mechanics, 2015)
Article introduces the Fast-Fourier transformation method (FFT) and an approximation method to calculate the conductivity of compound-inclusion composites in two-dimensional space. The approximation compares favorably with the numerical results for a number of periodic and random models over a range of volume proportions of phases, but divers at large volume proportions of the included phases when the interactions between the inclusions are more pronounced.